2012
DOI: 10.1111/j.1476-5381.2012.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three drugs for protecting against gentamicin‐induced hair cell and hearing losses

Abstract: BACKGROUND AND PURPOSE Exposure to an ototoxic level of an aminoglycoside can result in hearing loss. In this we study investigated the otoprotective efficacy of dexamethasone (DXM), melatonin (MLT) and tacrolimus (TCR) in gentamicin (GM)-treated animals and cultures. EXPERIMENTAL APPROACH Wistar rats were divided into controls (treated with saline); exposed to GM only (GM); and three GM-exposed groups treated with either DXM, MLT or TCR. Auditory function and cochlear surface preparations were studied. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 34 publications
1
51
1
1
Order By: Relevance
“…This model has been used and characterized in numerous studies (35)(36)(37). The present study demonstrated the occurrence of autophagy in this model using multiple techniques, including examination of autophagosomes by electron microscopy, immunofluorescence and immunoblot analysis of LC3-II formation.…”
Section: Discussionmentioning
confidence: 90%
“…This model has been used and characterized in numerous studies (35)(36)(37). The present study demonstrated the occurrence of autophagy in this model using multiple techniques, including examination of autophagosomes by electron microscopy, immunofluorescence and immunoblot analysis of LC3-II formation.…”
Section: Discussionmentioning
confidence: 90%
“…Among the earliest observations of free radical formation in OHCs after aminoglycoside treatment was in vitro formation of hydrogen peroxide and hydroxyl radicals in OHCs treated with gentamicin or kanamycin ; superoxide and hydrogen peroxide radicals were later shown to decrease auditory function in vivo (Clerici and Yang 1996). Production of ROS after gentamicin has been confirmed in other in vitro models (Basappa et al 2010;Sha and Schacht 1999a;Bas et al 2012), and ROS formation in the inner ear has been shown in tissues harvested from mice treated in vivo with kanamycin (Jiang et al 2005). ROS production may be secondary to actions of gentamicin as an iron chelator, as it appears that the irongentamicin complex drives free radical formation (Priuska and Schacht 1995).…”
Section: Introductionmentioning
confidence: 89%
“…When the nitric oxide (NO) inhibitor nitro-L-arginine methyl ester (L-NAME) was delivered via repeat injections through the tympanic membrane, L-NAME reduced gentamicin-induced hearing loss in the high-frequency range, but gave no protection in the middle or low frequencies (Nordang and Anniko 2005). A surgical approach to the cochlea to allow either gelfoam to be placed on the round or a drug delivery cannula to be inserted through the wall of the cochlea may have allowed agents including dexamethasone, melatonin, and tacrolimus to provide greater protection, but ABR thresholds were assessed using clicks, making frequency specific conclusions more difficult (Bas et al 2012). Therapeutic interventions that require surgical intervention are unlikely to have widespread clinical utility and they will be difficult to adopt in developing countries, where aminoglycoside use is greatest.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…After exposure to brimonidine, there is phosphorylation of the extracellular signal-activated kinases 1/2 (Erk1/2) in injured retinal homogenates [Fujita et al, 2013] or as a physiological response to α 2 -AR activation in uninjured retinal homogenates [Lai et al, 2002] and chicken Müller cells [HarunOr-Rashid et al, 2014]. Phosphorylation of Erk1/2 has especially been shown to mediate HC survival [Bas et al, 2012;Kurioka et al, 2015], and one way to protect OHCs from gentamicin-induced toxicity is increased activation of MAPK/Erk [Battaglia et al, 2003].…”
mentioning
confidence: 99%